2009
DOI: 10.1210/jc.2008-1772
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Serum Adiponectin with Skeletal Muscle Morphology and Insulin Sensitivity

Abstract: Circulating adiponectin concentrations were higher with increasing skeletal muscle capillary density and in individuals with higher proportion of slow oxidative muscle fibers. Furthermore, our results indicate that adiponectin could be a partial mediator of the relations between skeletal muscle morphology and insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…It is known that exogenously delivered adiponectin has similar effects on skeletal muscle that we observed in our CA-PPAR␥ animals, including activation of AMPK and ACC, reduced myocellular triglyceride content, altered fiber-type composition, increased expression of genes involved in lipid oxidation and mitochondrial function, and improved insulin sensitivity (21,37). Our model suggests that myocyte-produced adiponectin could provide an additional source of adiponectin signaling additive to the effect of circulating hormone.…”
Section: Discussionsupporting
confidence: 70%
“…It is known that exogenously delivered adiponectin has similar effects on skeletal muscle that we observed in our CA-PPAR␥ animals, including activation of AMPK and ACC, reduced myocellular triglyceride content, altered fiber-type composition, increased expression of genes involved in lipid oxidation and mitochondrial function, and improved insulin sensitivity (21,37). Our model suggests that myocyte-produced adiponectin could provide an additional source of adiponectin signaling additive to the effect of circulating hormone.…”
Section: Discussionsupporting
confidence: 70%
“…In contrast to results obtained with rodent muscle, similar AdipoR1 and AdipoR2 expression was observed in isolated muscle strips of type 2 diabetic and nondiabetic men [165]. A recent human study [166] revealed that circulating adiponectin concentrations were higher with increasing skeletal muscle capillary density and in individuals with higher proportions of slow oxidative muscle fibers, and that adiponectin could be a partial mediator of the relationship between skeletal muscle morphology and insulin sensitivity.…”
Section: Skeletal Musclementioning
confidence: 58%
“…More specifically, obese diabetic rats have only low oxidative type I fibers, whereas rats with hypertension or hyperlipidemia have both high oxidative type IIA and type IIC and low oxidative type I fibers in their skeletal muscles. The proportion of muscle fibers, as well as the capillary density in skeletal muscles is positively correlated with the levels of the circulating adiponectin, a hormone associated with insulin resistance and type II diabetes [25]. These studies showed that changes in the muscle fiber profile can result from metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 86%